Analisis Faktor Manajemen Keselamatan dalam Mitigasi Perilaku Tidak Aman Pekerja pada Operasi Migas Lepas Pantai Anjungan A PT. X - James Andry Doloksaribu; Dyan Kunthi Nugrahaeni; Novie Elvinawaty Mauliku; Budiman Budiman (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Unsafe behavior is widely recognized as the primary cause of workplace accidents. To encourage safe work practices, organizations must implement an effective safety management system that emphasizes strong leadership, clear communication, and genuine commitment to safety. This study aims to assess the influence of these three components, safety leadership, communication, and commitment on workers’ safety behavior. A cross-sectional design was employed, with data collected from 80 respondents at Platform A of PT. X through total sampling. The study used a structured questionnaire adapted from the 2024 Indonesia Oil and Gas Safety Management System Assessment Guidelines. The dependent variable was safety behavior. The independent variables included safety leadership, safety communication, and safety commitment. Data analysis involved univariate, bivariate (chi-square), and multivariate (binary logistic regression) techniques. Findings indicate that all three safety management components significantly impact workers’ safety behavior (p=0,0001). Among them, safety leadership emerged as the most influential factor (PR=12,701). Based on these results, it is recommended that PT. X strengthen its safety leadership practices through more proactive, consistent, and visible engagement by leaders in the field.